Evaluation of intra-abdominal solid organ injuries in children - Basaran, Ayse; Ozkan, Seda (Acta Biomedica Atenei Parmensis, 2019)
Aim: In our study we investigated characteristics and degree of intra-abdominal solid organ injuries according to tomographic imaging in pediatric patients who presented to our emergency clinic with possible abdominal injuries and to whom US and/or abdominal tomography were applied. Materials and Methods: 1066 pediatric patients were included in the study. The age, gender, injury localization, injury type, injury mechanism, abdominal US and CT results, and treatment specifics of patients were evaulated. Results: 58.5% of cases were male. Average age of children was 7.1±4.6 70.8% of the injuries occured in the outdoors. As for injury type, 92.8% of the injuries were blunt and 7.2% were penetrating traumas. The most common mechanism of injury was motor vehicle accidents at 41.4%. The most common abdominal physical examination finding was tenderness with a prevelance of 67%. In patients with solid organ injury, liver injury was detected in 47% of patients, spleen injury was detected in 36% of patients and renal injury was detected in 17% of patients. Grade II injury was the most common grade. 96.5 of patients were provided conservative treatment and 3.5% of patients were treated surgically. Conclusion: Solid organ injuries due to abdominal trauma in children are generally related to blunt trauma and are severe injuries. CT angio is an important imaging method for detecting solid organ injuries, classification of the injury and treatment determination. Greater than 90% of solid organ injuries in children can be treated successfully with conservative methods.